Application of the Gyrolab microfluidic platform to measure picomolar affinity of a PD-L1-binding Adnectin™ radioligand for positron emission tomography - Zhou Dai; Juhi Juneja; Lumelle Schneeweis; Daniel Cohen; Frank Marsilio; Paul Morin; Ruchira DasGupta (BioTechniques)
Advances in in vitro display and protein engineering yield therapeutics with affinities in the picomolar range. The Gyrolab® microfluidics platform uses the kinetic exclusion assay principle to measure subnanomolar solution affinities. This work describes application of the Gyrolab solution affinity module and the new multi-curve analysis feature to determine affinity of the PD-L1 Adnectin™ positron emission tomography radioligand, which was measured as 20 pM for human PD-L1. We also report key parameters that affect assay signal-to-background ratio and data quality, such as detection reagent concentration. Gyrolab offers the necessary throughput for rapid assay development with low sample consumption, as demonstrated in this study, which also provides helpful tips for assay optimization for solution affinity measurement.